Is the observable Universe consistent with the cosmological principle? - Kumar Aluri, Pavan; Cea, Paolo; Chingangbam, Pravabati; Chu, Ming-Chung; Clowes, Roger G; Hutsemékers, Damien; Kochappan, Joby P; Lopez, Alexia M; Liu, Lang; Martens, Niels C M; Martins, C.J.A.P.; Migkas, Konstantinos; et al. (Institute of Physics, 2023)
The cosmological principle (CP)—the notion that the Universe is spatially isotropic and homogeneous on large scales—underlies a century of progress in cosmology. It is conventionally formulated through the Friedmann-Lemaître-Robertson-Walker (FLRW) cosmologies as the spacetime metric, and culminates in the successful and highly predictive Λ-Cold-Dark-Matter (ΛCDM) model. Yet, tensions have emerged within the ΛCDM model, most notably a statistically significant discrepancy in the value of the Hubble constant, H 0. Since the notion of cosmic expansion determined by a single parameter is intimately tied to the CP, implications of the H 0 tension may extend beyond ΛCDM to the CP itself. This review surveys current observational hints for deviations from the expectations of the CP, highlighting synergies and disagreements that warrant further study. Setting aside the debate about individual large structures, potential deviations from the CP include variations of cosmological parameters on the sky, discrepancies in the cosmic dipoles, and mysterious alignments in quasar polarizations and galaxy spins. While it is possible that a host of observational systematics are impacting results, it is equally plausible that precision cosmology may have outgrown the FLRW paradigm, an extremely pragmatic but non-fundamental symmetry assumption.
This paper published with affiliation IIT (BHU), Varanasi in open access mode.
Keywords: anomalies; Cosmological Principle; FLRW